The Shifting Foreign Policy of Nepal: Impacts of Domestic Politics on International Relations (2000-2025) - Bhattarai, Bishnu Kumar; Bhandari, Anil Raj; Dahal, Chakraraj (Dristikon: A Multidisciplinary Journal, 2026)
The paper explores how Nepal’s transition from a monarchical regime to a federal democratic republic and the developing political instability have influenced its international relations. It explores evolving strategies of Nepal in balancing relations with India and China by using neorealist and constructivist theoretical lenses. It navigates regional and global pressures as well. This study reveals that domestic political actors, governments, parties, and leaders played decisive roles in shaping the foreign policy of Nepal. Each regime change brings adjustments in alignment. India’s and China’s strategic interests and rivalry, and the involvement of other powers like the United States, have further limited and influenced Nepal’s foreign policy choices. The findings of this study contribute to understanding how a small state’s quest for autonomy and security is mediated by domestic politics and external forces and circumstances. Although the geographic and economic constraints limit the extent of realignment, the study concludes that foreign policy shifts of Nepal reflect a hedging approach that aims at maximizing strategic autonomy.